DIGITAL VILLAGES AS A MODEL OF RURAL INNOVATION: GOVERNANCE EXPERIENCES FROM PUNGGUL, BALI - Ni Putu Mirna Sari; I Gusti Ayu Agung Dewi Sucitawathi Pinatih (Universitas Negeri Yogyakarta, 2026)
The increasing urgency of digital transformation in Indonesia has emphasized the need for innovation at the village level, where most of the country’s population resides. This study aims to examine how rural digital governance is institutionalized through the case of Punggul Village in Badung, Bali, which has been nationally recognized as a model of digital village development. Employing a qualitative case study approach, the research collected data through interviews, observation, and document analysis to understand governance dynamics, leadership roles, and community participation in digital transformation. The findings reveal that Punggul’s success stems from the integration of transformational leadership, institutional entrepreneurship, and participatory collaboration that fostered a culture of digital governance. Rather than focusing solely on technology, the transformation process emphasized human resource development, transparency, and adaptive institutional learning. The study proposes a model of rural digital innovation that highlights how technology, culture, and governance co-evolve to create sustainable public value. This research contributes to the discourse on digital governance by demonstrating that rural innovation can emerge from community-driven processes supported by leadership and cultural values, offering practical insights for scaling digital village initiatives in developing countries.